2005
DOI: 10.1159/000085385
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Activities of Green Tea Catechins in Neuroprotection

Abstract: Many lines of evidence suggest that oxidative stress resulting in reactive oxygen species (ROS) generation and inflammation play a pivotal role in the age-associated cognitive decline and neuronal loss in neurodegenerative diseases including Alzheimer’s (AD), Parkinson’s (PD) and Huntington’s diseases. One cardinal chemical pathology observed in these disorders is the accumulation of iron at sites where the neurons die. The buildup of an iron gradient in conjunction with ROS (superoxide, hydroxyl radical and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(119 citation statements)
references
References 129 publications
(147 reference statements)
2
116
0
1
Order By: Relevance
“…2, A, B, and D) sustains high concentration of intracellular iron produced by HO-1 catalytic activity that may result in phosphorylation of PKC␣ and subsequent activation of Nrf2 (48,51). In this scenario, we speculated that EGCG, as an iron chelator (26,33) and not as an ROS generator (36,37), may exert its inhibitory effects on phosphorylation of PKC␣ (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…2, A, B, and D) sustains high concentration of intracellular iron produced by HO-1 catalytic activity that may result in phosphorylation of PKC␣ and subsequent activation of Nrf2 (48,51). In this scenario, we speculated that EGCG, as an iron chelator (26,33) and not as an ROS generator (36,37), may exert its inhibitory effects on phosphorylation of PKC␣ (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…observed unexpectedly low levels of ferritin in contrast to overexpression of HO-1 (Fig. 2, B and D), we next focused on the possibility that the occurrence of highly activated PKC␣ may be associated with an accumulation of free iron (48,51) because of the failure of iron sequestering by ferritin, which is concomitantly up-regulated with HO-1 induction (3,54). To verify this hypothesis, we tested the effect of an iron chelator, DFO (26), along with an ROS scavenging agent, NAC (20,21), during EGCG treatment of A549 cells.…”
Section: High Concentration Of Egcg Blocks Overexpression Of Ho-1 Viamentioning
confidence: 99%
“…Neuronal cells exposed to H 2 O 2 produce membrane depolarization depending on the increased permeability to Na 14) It could be also suggested that ROS-scavenging activity of SR possibly attributable to catechin played a critical role in neuronal survival, since catechin has been shown to have neuroprotective property directly associated with ROS-scavenging activity. 46,47) Future study to elucidate the precise mechanism should be performed.…”
Section: Sr Protects Rat Brain Against Mcao-induced Focalmentioning
confidence: 99%
“…It contains polyphenols and other metabolites, with anti-carcinoma (Wang and Bachrach, 2002;Zhang et al, 2012), anti-oxidative (Rietveld and Wiseman, 2003;Fatima and Rizvi, 2015) and anti-arteriosclerosis (Lee et al, 2015) properties. These polyphenols are also reported to be effective for the prevention of Alzheimer's and Parkinson diseases (Mandel, Amit, Weinreb, Reznichenko, and Youdim, 2008;Anandhan, Tamilselvam, Radhiga, Rao, and Essa, 2012) and for their anti-obesity effects in human and animals (Zhong, Furne, and Levitt, 2006;Ashigai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%